Do Caste and Class Define Inequality? Revisiting Education in a Kerala Village. (July 2014) - Scaria, Suma
Is there a strong correlation between caste and class in access to education, especially higher education? This is the broader question addressed by the study in the context of Kerala, the southernmost state in India, with impressive conventional indicators in education. Micro-level insights based on the study of a village in Kerala show that old forms of inequalities have been replaced by new forms of inequalities in education. Notwithstanding Kerala's impressive indicators, huge inequalities exist in the educational attainments of the population. The Scheduled Castes (SCs) are still at the bottom of the rankings in enrolment in higher education despite the adoption of a positive discrimination policy and educational subsidy by the state. This situation is explained through an examination of three issues: the perception of the lower employment potential of conventional or mainstream higher education; the educational polices of the state and disparate access to economic resources. The study concludes by offering a few policy recommendations to make higher education more inclusive for marginalised sections of society.